Pulmonary Autograft Dilatation and its Risk Factors After Classical Ross Procedure: a Retrospective Single Center Study - I. I. Chernov; S. T. Enginoev; S. S. Ekimov; T. K. Rashidova; U. K. Abdulmedzhidova; M. A. Guliyev; A. A. Ziankou; A. B. Gamzaev (Креативная хирургия и онкология, 2023)
Introduction. Aortic valve replacement with pulmonary autograft (Ross procedure) demonstrated excellent immediate and long-term results. Dilation of the pulmonary autograft in the long-term period is the main reason for repeated surgery. Aim: to study the prevalence of pulmonary autograft dilatation and its risk factors.   Materials and methods. From April 2009 to December 2022, 158 patients underwent classical Ross surgery. Inclusion criteria: patients aged 18 and older, patients who underwent classical surgery. Exclusion criteria: patients under 18, modifi ed methods of Ross procedure. Follow-up period: 104 (49–124) months.   Results and discussion. The median age of patients was 33 (25–43) years. Hospital mortality accounted for 0.6 %. Perioperative myocardial injury was 3.8 %, conduction disorder requiring permanent pacemaker implantation accounted for 1.9 %, the incidence of strokes and acute kidney injury requiring hemodialysis was 0.6 %. Ten-year freedom from autograft reoperation was 88.4. Ten-year freedom from reoperation for aortic aneurysm accounted for 92 %. Predictors of autograft dilatation in the long-term period were: age (OR: 0.942; 95% CI: 0.901–0.984, p = 0.008) and the initial size of sinuses of Valsalva (OR: 1.18; 95% CI: 1.027–1.215, p = 0.01).   Conclusion. Ten-year freedom from autograft reoperation due to aortic dilatation and freedom from aortic dilatation ≥ 45 mm was 92 % and 37.2 %, respectively. The main predictors of autograft dilatation in the postoperative period are the age and the initial diameter of the sinuses of Valsalva.